Structural studies on enzymes involved in microbial hydrogen sulfide metabolism - Soares Costa, Sofia (2021)
"Hydrogen sulfide (H2S) is an ancient molecule present since Earth’s primordial atmosphere. Organisms from all Domains of Life early evolved to use this molecule in their physiologic activities. H2S was first recognized as a potent respiratory toxin, however, recent studies revealed its involvement in processes such as neurotransmission, signaling and inflammation. Therefore, a tight regulation of H2S intracellular concentration is paramount in all organisms.(...)"